Role of Leptin in Cardiovascular Diseases - Poetsch, Mareike S.; Strano, Anna; Guan, Kaomei (Frontiers in Endocrinology, 2020)
The adipocyte-derived adipokine leptin exerts pleiotropic effects, which are essential for the regulation of energy balance and cell metabolism, for controlling inflammatory and immune responses, and for the maintenance of homeostasis of the cardiovascular system. Leptin resistance in obese or type 2 diabetes mellitus (T2DM) patients is defined as a decrease in tissue response to leptin. In the cardiovascular system, leptin resistance exhibits the adverse effect on the heart’s response to stress conditions and promoting cardiac remodeling due to impaired cardiac metabolism, increased fibrosis, vascular dysfunction, and enhanced inflammation. Leptin resistance or leptin signaling deficiency results in the risk increase of cardiac dysfunction and heart failure, which is a leading cause of obesity- and T2DM-related morbidity and mortality. Animal studies using leptin- and leptin receptor- (Lepr) deficient rodents have provided many useful insights into the underlying molecular and pathophysiological mechanisms of obese- and T2DM-associated metabolic and cardiovascular diseases. However, none of the animal models used so far can fully recapitulate the phenotypes of patients with obese or T2DM. Therefore, the role of leptin in the human cardiovascular system, and whether leptin affects cardiac function directly or acts through a leptin-regulated neurohumoral pathway, remain elusive. As the prevalence of obesity and diabetes is continuously increasing, strategies are needed to develop and apply human cell-based models to better understand the precise role of leptin directly in different cardiac cell types and to overcome the existing translational barriers. The purpose of this review is to discuss the mechanisms associated with leptin signaling deficiency or leptin resistance in the development of metabolic and cardiovascular diseases. We analyzed and comprehensively addressed substantial findings in pathophysiological mechanisms in commonly used leptin- or Lepr-deficient rodent models and highlighted the differences between rodents and humans. This may open up new strategies to develop directly and reliably applicable models, which resemble the human pathophysiology in order to advance health care management of obesity- and T2DM-related cardiovascular complications.